Regulation of Cell Proliferation and Differentiation by PPARβ/δ - Rolf Müller; Markus Rieck; Sabine Müller-Brüsselbach (PPAR Research)
Peroxisome proliferator-activated receptor-β/δ (PPARβ/δ) is a ligand-activated transcription factor with essential functions in the regulation of lipid catabolism, glucose homeostasis, and inflammation, which makes it a potentially relevant drug target for the treatment of major human diseases. In addition, there is strong evidence that PPARβ/δ modulates oncogenic signaling pathways and tumor growth. Consistent with these observations, numerous reports have clearly documented a role for PPARβ/δ in cell cycle control, differentiation, and apoptosis. However, the precise role of PPARβ/δ in tumorigenesis and cell proliferation remains controversial. This review summarizes our current knowledge and proposes a model corroborating the discrepant data in this area of research.